Dissociation of methane under high pressure - Gao, Guoying; Oganov, Artem R; Ma, Yanming; Wang, Hui; Li, Peifang; Li, Yinwei; Iitaka, Toshiaki; Zou, Guangtian (The Journal of chemical physics, 2010)
Methane is an extremely important energy source with a great abundance in nature and plays a significant role in planetary physics, being one of the major constituents of giant planets Uranus and Neptune. The stable crystal forms of methane under extreme conditions are of great fundamental interest. Using the ab initio evolutionary algorithm for crystal structure prediction, we found three novel insulating molecular structures with P2(1)2(1)2(1), Pnma, and Cmcm space groups. Remarkably, under high pressure, methane becomes unstable and dissociates into ethane (C(2)H(6)) at 95 GPa, butane (C(4)H(10)) at 158 GPa, and further, carbon (diamond) and hydrogen above 287 GPa at zero temperature. We have computed the pressure-temperature phase diagram, which sheds light into the seemingly conflicting observations of the unusually low formation pressure of diamond at high temperature and the failure of experimental observation of dissociation at room temperature. Our results support the idea of diamond formation in the interiors of giant planets such as Neptune.